2005
DOI: 10.1097/01202412-200511000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Anteversion of the acetabulum and femoral neck in early walking age patients with developmental dysplasia of the hip

Abstract: Computed tomography measurements were made to quantify the relationship between the anteversion of the acetabulum and femoral neck in 27 early walking age patients (age range; 18-48 months) with developmental dysplasia of the hip. The centre-edge angle and acetabular index were measured in standard pelvis radiographs, and anteversion of acetabulum and femoral neck were measured by use of two-dimensional computed tomography in 25 complete dislocated, 19 subluxated and 10 unaffected hips (a total of 54 hips). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…We would like to know whether any radiographic analysis was done preoperatively to assess the femoral anteversion. In our experience, we found that femoral anteversion is rarely exaggerated in DDH of the early walking age group,2 and this is in coordinance with other radiographic studies 34. Secondly, the author's method of assessing the need for derotation seems a little unclear.…”
supporting
confidence: 72%
“…We would like to know whether any radiographic analysis was done preoperatively to assess the femoral anteversion. In our experience, we found that femoral anteversion is rarely exaggerated in DDH of the early walking age group,2 and this is in coordinance with other radiographic studies 34. Secondly, the author's method of assessing the need for derotation seems a little unclear.…”
supporting
confidence: 72%
“…In a recent study open reduction without simultaneous femoral osteotomy strongly predicted the need for a secondary procedure, and the authors concluded there should be a low threshold to performing femoral osteotomy during a primary open reduction [136] . Although generally accepted that DDH is associated with increased femoral anteversion, some studies did not show a difference in anteversion compared with normal hips [137,138] while others did [139] . Therefore, the indications for femoral derotational osteotomy remain unclear.…”
Section: Open Reduction and Hip Reconstructionmentioning
confidence: 99%
“…A previous study suggests that although femoral version is increased in children with developmental dysplasia of the hip, there is not a significant difference between those with subluxated and dislocated hips. 13 A further weakness is the decision to use the center of the physis as a proxy for the center of the head in all hips in part II of the study. However, this method was equivalent to Mose circles in subluxated hips, very close to the center in dislocated hips and is significantly more practical for clinicians to apply.…”
Section: Discussionmentioning
confidence: 99%